Microbiology and Chemical Quality of Drinking Water From Household-Level Distribution Network - Suryatri Darmiatun (Graduate Program, 2017)
Quality of most of drinking water supply from the household-level distribution network deteriorates before being distributed to the consumers. The water supply was not hygenic, tasted bad and had strong odor. The purpose of this study was determining the microbiological and chemical contamination of drinking water from distribution network. The study was a descriptive study which employed documentation as the data collection method. Parameters that will be analized were microbiological and chemical quality. The data analysis method was descriptive analysis was used. The findings showed some potential contaminations such as (1) the indicators of the biological quality of the water were the number and growth of bacteria in the biofilms (bacterial colony formation) triggered by temperature of water, nutrients in the water, quality of the pipe, and water flow; (2) the indicators of the chemical quality of the water were Volatile Organic Compounds (VOCs) substance exposure, Assimilable Organic Carbon (AOC) and loss of metal from the type of pipe used. The preventive measures were to evaluate quality of drinking water before being distributed to the household-level network, conduct certain method of water treatment when necessary, analyze materials and characteriristics of the water pipes, install the pipes appropriately, conduct the pressure test for control and maintenance for the utilities (tap).Keywords: biofilm, drinking water, pipe